2018
DOI: 10.1186/s13005-018-0179-z
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional evaluation of soft tissue after orthognathic surgery

Abstract: BackgroundTo evaluate the nasolabial soft tissue change three-dimensionally after orthognathic surgery, using a structured light scanner.MethodsThirty-two malocclusion patients, who underwent orthognathic surgery, were evaluated. CBCT and 3D facial scans were obtained before surgery and 3 months after surgery. The 3D changes in the 26 landmarks, and the relative ratio of the soft tissue movement to the bony movement, were evaluated.ResultsIn the Le Fort I advancement patients, the nasal tip moved 17% forward, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 31 publications
0
32
0
3
Order By: Relevance
“…Jung et al concluded that the accuracy of the structured light system is comparable to the direct anthropometric measurements. Furthermore, it was reported that more reliable 3D datasets are expected if the face of the subject was scanned from a couple of angles at the same time in less than 1 s [ 17 ]. Lee et al investigated the reliability of 34 facial landmarks using a 3D handheld structured-light scanner (Artec Eva) and they observed constellations of landmarks that showed high reliability in each condition in terms of head posture and image resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jung et al concluded that the accuracy of the structured light system is comparable to the direct anthropometric measurements. Furthermore, it was reported that more reliable 3D datasets are expected if the face of the subject was scanned from a couple of angles at the same time in less than 1 s [ 17 ]. Lee et al investigated the reliability of 34 facial landmarks using a 3D handheld structured-light scanner (Artec Eva) and they observed constellations of landmarks that showed high reliability in each condition in terms of head posture and image resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Further advantages include short scan time, portability, ease of operation, and reasonable cost [ 16 ]. Jung et al found that the accuracy of structured light systems compares to that of direct anthropometric measurements and concluded that it is a reliable approach for a facial soft tissue assessment [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…3D CT images were commonly used to analyze facial soft tissue changes after surgery [28, 29]; Jeon et al [12] analyzed the perioral lip landmarks on three-dimensional image from cone-beam computed tomography taken before and 6 months after the operation. 3D facial soft tissue scan images before and after surgery have been also used to evaluate postoperative changes of soft tissue [30, 31]. Jung et al [30] investigated the 3D changes in the 26 landmarks, and the relative ratio of the soft tissue movement to the bony movement was evaluated with CBCT and 3D facial scan images.…”
Section: Discussionmentioning
confidence: 99%
“…3D facial soft tissue scan images before and after surgery have been also used to evaluate postoperative changes of soft tissue [30, 31]. Jung et al [30] investigated the 3D changes in the 26 landmarks, and the relative ratio of the soft tissue movement to the bony movement was evaluated with CBCT and 3D facial scan images. However, those studies focused on analyzing the changes of facial soft tissue in the anterior-posterior direction.…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the Ethics Committee of Peking University School and Hospital of Stomatology (PKUSSIRB-201948110). The sample size of this preliminary study was determined according to historical studies (Solem RC et al [11]: 24 subjects; Jung J et al [12]: 32 subjects; Li H et al [13]: 50 subjects).…”
Section: Subjectsmentioning
confidence: 99%